计算:(1) ( 1 2 - 1 3 )÷(- 1 6 )+ (-2) 2 ×(-14) (2) (-5)×(-
计算:(1)(12-13)÷(-16)+(-2)2×(-14)(2)(-5)×(-16-320+45-1112)×12(3)(-1)2011-(1-0.5)×15×[3-...
计算:(1) ( 1 2 - 1 3 )÷(- 1 6 )+ (-2) 2 ×(-14) (2) (-5)×(- 1 6 - 3 20 + 4 5 - 11 12 )×12 (3) (-1) 2011 -(1-0.5)× 1 5 ×[3- (-2) 2 ] (4)-(-10) 2 +[(-4) 2 -(1-3 2 )×2].
展开
道德人自同行4653
推荐于2016-05-20
·
TA获得超过312个赞
知道答主
回答量:186
采纳率:50%
帮助的人:136万
关注
(1)原式=( - )×(-6)+4×(-14)=-3+2-56=-57; (2)原式=(-60)×(- - + - )=10+9-48+55=26; (3)原式=-1- × ×(-1)=- ; (4)原式=-100+16-(-8)×2=-100+16+16=-68. |
收起
为你推荐: